Ancestor approved : intertribal stories for kids - Smith, Cynthia Leitich (New York : Heartdrum, 2021)
Presents sixteen short stories and two poems that look at the hope, joy, resilience, the strength of community, and Native American pride.
What is a Powwow? / Kim Rogers -- Fancy dancer / Monique Gray Smith -- Flying together / Kim Rogers -- Warriors of forgiveness / Tim Tingle -- Brothers / David A. Robertson -- Rez dog rules / Rebecca Roanhorse -- Secrets and surprises / Traci Sorell -- Wendigos don't dance / Art Coulson -- Indian price / Eric Gansworth -- Senecavajo: Alan's story / Brian Young -- Squash Blossom bracelet: Kevin's story / Brian Young -- Joey reads the sky / Dawn Quigley -- What we know about glaciers / Christine Day -- Little Fox and the case of the missing regalia / Erika T. Wurth -- The ballad of Maggie Wilson / Andrea L. Rogers -- Bad dog / Joseph Bruchac -- Between the lines / Cynthia Leitich Smith -- Circles / Carole Lindstrom.
Library Media Connection starred, January 2021
4.5
3-6
Keywords: Powwows -- Juvenile fiction; Communities -- Juvenile fiction; Indigenous people of North America -- Juvenile fiction; Powwows -- Fiction; Social groups -- Fiction; Indigenous people of North America -- Fiction; Short stories